The Association Between Regional Macula Vessel Density and Central Visual Field Damage in Advanced Glaucoma Eyes. Issue 9 (2nd September 2022) - Ghahari, Elham; Bowd, Christopher; Zangwill, Linda M.; Proudfoot, James A.; Penteado, Rafaella C.; Kyung, Haksu; Hou, Huiyuan; Moghimi, Sasan; Weinreb, Robert N.
Abstract : Précis: Both macular superficial vessel density and ganglion cell complex (GCC) thickness measurement are significantly associated with regional and global 10-degree central visual field (VF) sensitivity in advanced glaucoma. Purpose: The purpose of this study was to evaluate the regional and global structure-function relationships between macular vessel density (MVD) assessed by optical coherence tomography angiography (OCTA) and 10-2 VF sensitivity in advanced open angle glaucoma eyes. Methods: Macular OCTA and 10-2 VF sensitivity of 44 patients [mean deviation (MD) <−10 dB] were evaluated. Regional and global VF mean sensitivity (MS) was calculated from total deviation plots. Superficial and deep MVD were obtained from 3× 3 and 6×6 mm 2 OCTA scans using 2 sectoral definitions. Spectral-domain optical coherence tomography macular GCC thickness was obtained simultaneously from the same scan as the MVD measurements. Linear regression models were used to assess the associations ( R 2 ). Results: Lower MS was significantly associated with a reduction in superficial MVD and GCC in each region of both scan sizes for both maps. Associations were weaker in the individual sectors of the whole image grid than the Early Treatment Diabetic Retinopathy Study map. Deep-layer MVD was not associated with central MS. Although 6×6 mm 2 and perifoveal vessel density had better associations with central 10-degree MS compared with GCC thickness (eg, R 2 from 25.7 to 48.1 µm and 7.8% to 32.5%, respectively), GCC associations were stronger than MVD associations in the central 5-degree MS. Conclusions: Given a stronger MVD-central 10-degree VF association compared with GCC, as well as stronger GCC-central 5-degree VF association compared with MVD, MVD and GCC are complementary measurements in eyes with advanced glaucoma. A longitudinal analysis is needed to determine the relative utility of the GCC and MVD measurements.